World's end - Chadbourn, Mark. (London : Victor Gollancz, 1999)
Five people, bound together by an age-old mythic heritage, learn they hold the key to the future when the gods of ancient Celtic mythology and creatures of folklore return, creating havoc in the modern world.
Library Journal
Adult.
Adult
Keywords: Good and evil -- Fiction; Good and evil -- Fiction; Fantastic fiction; Fantastic fiction